Exosomes Immunity Strategy: A Novel Approach for Ameliorating Intervertebral Disc Degeneration - Li, Weihang; Zhang, Shilei; Wang, Dong; Zhang, Huan; Shi, Quan; Zhang, Yuyuan; Wang, Mo; Ding, Ziyi; Xu, Songjie; Gao, Bo; Yan, Ming (Frontiers in Cell and Developmental Biology, 2022)
Low back pain (LBP), served as one of the most severe medical and social problems globally, has affected nearly 80% of the population worldwide, and Intervertebral disc degeneration (IDD) is a common musculoskeletal disorder which happens to be the primary trigger of LBP. The pathology of IDD is based on the impaired homeostasis of catabolism and anabolism in the extracellular matrix (ECM), uncontrolled activation of immunologic cascades, dysfunction and loss of nucleus pulposus (NP) cells in addition with dynamic cellular and biochemical alterations in the microenvironment of intervertebral disc (IVD). Currently, the therapeutic approaches regarding IDD mainly targeting on surgical intervention with minority of anti-inflammation or pain-relieving choices, while both of these approaches could not make a considerable cure to IDD. Exosomes, extracellular vesicles with a diameter of 30-150 nm, are secreted by various kinds of cell types like stem cells, tumor cells, immune cells, and endothelial cells, the lipid bilayer of the exosomes protect them from ribonuclease degradation and help improve their biological efficiency in recipient cells. Increasing evidences have reported the promising applications of exosomes in immunological diseases, and regarded exosomes as a potential therapeutic approach for IDD. This review focus on providing the novel approach of exosomes’ therapy from different cell sources, to clarify the essential roles of exosomes in regulating IDD, especially immunologic strategy.